Analisis Tingkat Budaya Gaya Hidup Aktif Generasi Z pada Pengguna Aplikasi STRAVA di Kota Bandung - Fajar Cahya Gumilang; Mirna Nur Alia Abdullah; Faja Nugraha Asyahidda (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aims to describe the level of active lifestyle culture among Generation Z Strava users in Bandung City, a topic that remains rarely examined in this specific local context. The novelty of this article lies in positioning active lifestyle culture as a construct measured through three indicators simultaneously, namely the regularity of physical activity, the habituation of physical activity in daily life, and health values and responsibility, rather than mere exercise frequency. This study employed a descriptive quantitative approach using a Likert-scale questionnaire distributed to 150 Generation Z respondents from two sports communities in Bandung City. The six-item instrument was valid and reliable (Cronbach's Alpha of 0.851). The total variable score fell into the high category (mean of 23.51 within a theoretical range of 6-30), with 74.67% of respondents in the high category and a smaller proportion in the moderate and low categories. These findings indicate that the respondents studied tend to demonstrate regularity, habitual engagement, and value-based awareness in maintaining an active lifestyle, underscoring the potential of digital fitness applications as a medium that supports the formation of this culture among urban Generation Z.